(untitled) (Global Journal of Advanced Engineering Technologies and Sciences, 2019)
This paper presents the experimental study on surface roughness in MQCL hard milling of Hardox 500 steel by using Al2O3 emulsion-based nanofluid. Box-Behnken experimental design and ANOVA analysis are used to investigate the influence of investigated factors on surface roughness. The obtained results indicate that feed rate hasa strong effect on surface roughness. Moreover, in the investigated range, Ra value is smallest at cutting speed of 105 m/min and is about 0.102 µm – 0.374 µm, which is equivalent to grinding. It is also proven that cutting performance improves due to the better cooling and lubricating effects of Al2O3 nanofluid. In this study, the novel alternative solution for difficult-to-cut material like Hardox 500 steel is presented while retaining the environmentally friendly character.